Early Delivery or Expectant Management for Late Preterm Preeclampsia: A Meta-Analysis of Randomized Controlled Trials. Issue 2 (February 2022) - Chatzakis, Christos; Liberis, Anastasios; Zavlanos, Apostolos; Petousis, Stamatis; Tsakmaki, Evangelia; Dinas, Konstantinos; Sotiriadis, Alexandros
Abstract : (Abstracted from Acta Obstet Gynecol Scand 2021;100:1392–1400) Worldwide, preeclampsia affects approximately 4.5% of pregnancies. Weighing the maternal benefit of immediate delivery with the risk of severe neonatal complications is important to determine the appropriate time to deliver in cases of preeclampsia.